After empire : the conceptual transformation of the Chinese state, 1885-1924 - Zarrow, Peter Gue (Stanford University Press, 2012)
From 1885-1924, China underwent a period of acute political struggle and cultural change, brought on by a radical change in thought: after over 2,000 years of monarchical rule, the Chinese people stopped believing in the emperor. These forty years saw the collapse of Confucian political orthodoxy and the struggle among competing definitions of modern citizenship and the state. What made it possible to suddenly imagine a world without the emperor?